A Study on AI: Customer Feedback & Personalized Marketing Comparison between India and Nigeria - Patel, Dr. Ajay Kumar; Agarwal, Dr. Vaishali; Lohar, Harsh Kumar; Jha, Shivani (Journal of International Conference Proceedings, 2023)
In the world of business, using Artificial Intelligence (AI) has really changed how companies connect with customers. This research looks at how AI can understand what customers think and how it helps make marketing more personal. It explores how AI tools can learn important things from customer feedback, like what people like and how they feel. Then, comes how companies can uses these things to make marketing that feels special to each customer. Further, this shows the customer perspective and loyalty along with comparative study of India's AI personalized marketing with Nigeria's AI personalized marketing, by looking at real examples from different businesses. This helps companies build strong relationships with customers and be better than their competitors in today's world that uses a lot of data. The research findings help us see how AI and understand customer feedback are super important for making customers happy and loyal to a brand.